(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2010)
Neurospora crassa, a non-pathogenic filamentous fungus produces hydrolytic enzymes (cellulase, xylanase, etc.) and is capable to convert lignocellulosic materials (cellulose, xylan) into simple sugars. Carboxymethylcellulase (CMCase) and xylanase activities were evaluated using 4 morphological mutants of N. crassa induced with leaf extract of Abroma augusta L in comparison to the wild type (Ema). Enzymatic activity was expressed as International Unit (IU). It was found that N. crassa mycelia secrete cellulases (CMCase) and xylanases to the culture supernatant. Wild N. crassa (Ema) showed highest cellulase activity (0.066 IU) and mutant ro 197 showed lowest (0.013 IU) activity. In case of xylanase, wild showed highest (0.313 IU) and mutant ro 197 showed lowest (0.088 IU) activity. These enzymatic assays revealed that wild and mutants of N. crassa possess detectable cellulase and xylanase activity. Key words: Mutants; Neurospora crassa; Enzyme activities DOI: 10.3329/bjsir.v45i2.5713 Bangladesh J. Sci. Ind. Res. 45(2), 151-154, 2010